Systematic review of factors influencing the effectiveness of the co-operative board - Mokhtaruddin Buang (AECOOP Escuela de Estudios Cooperativos, 2020)
Co-operatives played a significant part of the global economy, and its success depends on the effectiveness of the co-operative board to perform their roles. This article is aimed at reviewing and synthesizing the literature of the last ten years in order to enhance our understanding of the factors that have affected the effectiveness of the board. A systematic review of the Scopus and Web of Science databases identified 13 related studies that respond to research questions, guided by the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. An analysis of these articles resulted in four main themes – board composition, board characteristics, board structure and board process, and these four themes formed a total of 12 sub-themes. This study has three significant contributions. Firstly, it provides an overview of studies of the co-operative board. Second, this systematic review highlighted the factors impacting the board's effectiveness. Finally, derived from this systematic analysis, we draw the pattern of variables that were analyzed in assessing the efficacy of the co-operative board. The findings indicated that the studies of the co-operative board are still inadequate, and in the context of developing countries, empirical research lags even further behind. Most studies concentrate mainly on the effect of board characteristics, followed by board composition, board process and board structure. Some recommendations for future research are outlined to explore other related factors that may enhance the co-operative board's effectiveness, namely from the perspective of the resource provision role of directors.